Does fishery management for groupers (Teleostei: Epinephelidae) protect them effectively? Context from the IUCN's Red list of threatened species - Sean T. Fennessy; Christi Linardich; Kevin Rhodes; Joao P. Barreiros; David Pollard; Eloy Sosa-Cordero; Felicia Coleman; Alfonso Aguilar-Perera; Christopher R. Malinowski; Thierry Brulé; Pedro Afonso; Kayan Ma; et al. (Ocean & Coastal Management, 2026)

eDNA2IQI: an eDNA/random forest-based prediction tool that accurately predicts ecological status for regulatory-compliance assessment - A.J. Wyness; T. Stoeck; B.J. Morrissey; I. Berrill; K. Davidson; C. FairBairn; S. MacIntyre; C. Webb; T. Foster; S. Brain; D. Svobodova; C. Clark; et al. (Aquaculture, 2026)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Studying the Role Race Plays in Food Insecurity in United States as Well as the Effect of Levels of Education on Race and Food Insecurity and Its Implications - H. Patel; P. Pollard (Journal of the Academy of Nutrition and Dietetics, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

Comment on Bachmann et al. (2013): A nonrepresentative sample cannot describe the extent of cultural eutrophication of natural lakes in the United States - Cory P. McDonald; Noah R. Lottig; John L. Stoddard; Alan T. Herlihy; Sarah Lehmann; Steven G. Paulsen; David V. Peck; Amina I. Pollard; R. Jan Stevenson (Limnology and Oceanography, 2014)

Protecting asset value and driving performance with a dynamic, risk-based contingency fund - C. W. Mauelshagen; S. J. T. Pollard; D. Owen; S. Herndlhofer; P. Firth; J. McKenna; N. Bingley; P. Jenson (Environment Systems and Decisions, 2014)

A method for estimating colony sizes of Adélie penguins using remote sensing imagery - M. A. LaRue; H. J. Lynch; P. O. B. Lyver; K. Barton; D. G. Ainley; A. Pollard; W. R. Fraser; G. Ballard (Polar Biology, 2014)

Biofilm functional responses to the rehydration of a dry intermittent stream - Xisca Timoner; V. Acuña; L. Frampton; P. Pollard; S. Sabater; S. E. Bunn (Hydrobiologia, 2014)

Fishing groupers towards extinction: a global assessment of threats and extinction risks in a billion dollar fishery - Yvonne Sadovy de Mitcheson; Matthew T Craig; Athila A Bertoncini; Kent E Carpenter; William W L Cheung; John H Choat; Andrew S Cornish; Sean T Fennessy; Beatrice P Ferreira; Philip C Heemstra; Min Liu; Robert F Myers; et al. (Fish and Fisheries, 2013)
Groupers are a valuable fishery resource of reef ecosystems and are among those species most vulnerable to fishing pressure because of life history characteristics including longevity, late sexual maturation and aggregation spawning. Despite their economic importance, few grouper fisheries are regularly monitored or managed at the species level, and many are reported to be undergoing declines. To identify major threats to groupers, the International Union for Conservation of Nature (IUCN) Red List criteria were applied to all 163 species. Red List assessments show that 20 species (12%) risk extinction if current trends continue, and an additional 22 species (13%) are considered to be Near Threatened. The Caribbean Sea, coastal Brazil and Southeast Asia contain a disproportionate number of Threatened species, while numerous poorly documented and Near Threatened species occur in many regions. In all, 30% of all species are considered to be Data Deficient. Given that the major threat is overfishing, accompanied by a general absence and/or poor application of fishery management, the prognosis for restoration and successful conservation of Threatened species is poor. We believe that few refuges remain for recovery and that key biological processes (e.g. spawning aggregations) continue to be compromised by uncontrolled fishing. Mariculture, through hatchery‐rearing, increases production of a few species and contributes to satisfying high market demand, but many such operations depend heavily on wild‐caught juveniles with resultant growth and recruitment overfishing. Better management of fishing and other conservation efforts are urgently needed, and we provide examples of possible actions and constraints.

Production and Quality Assurance of Solid Recovered Fuels Using Mechanical—Biological Treatment (MBT) of Waste: A Comprehensive Assessment - C. A. Velis; P. J. Longhurst; G. H. Drew; R. Smith; S. J. T. Pollard (Critical Reviews in Environmental Science and Technology, 2010)

The chronology of abrupt climate change and Late Upper Palaeolithic human adaptation in Europe - S. P. E. Blockley; S. M. Blockley; R. E. Donahue; C. S. Lane; J. J. Lowe; A. M. Pollard (Journal of Quaternary Science, 2006)
This paper addresses the possible connections between the onset of human expansion in Europe following the Last Glacial Maximum, and the timing of abrupt climate warming at the onset of the Lateglacial (Bölling/Allerød) Interstadial. There are opposing views as to whether or not human populations and activities were directly ‘forced’ by climate change, based on different comparisons between archaeological and environmental data. We review the geochronological assumptions and approaches on which data comparisons have been attempted in the past, and argue that the uncertainties presently associated with age models based on calibrated radiocarbon dates preclude robust testing of the competing models, particularly when comparing the data to non‐radiocarbon‐based timescales such as the Greenland ice core records. The paper concludes with some suggestions as to the steps that will be necessary if more robust tests of the models are to be developed in the future. Copyright © 2006 John Wiley & Sons, Ltd.

Gene expression and genotyping studies implicate the interleukin 7 receptor in the pathogenesis of primary progressive multiple sclerosis - D. R. Booth; A. T. Arthur; S. M. Teutsch; C. Bye; J. Rubio; P. J. Armati; J. D. Pollard; R. N. S. Heard; G. J. Stewart (Journal of Molecular Medicine, 2005)

A comparison of fish assemblages associated with different riparian vegetation types in the Hawkesbury–Nepean River system - I. Growns; P. C. Gehrke; K. L. Astles; D. A. Pollard (Fisheries Management and Ecology, 2003)
Fish assemblages in six reaches of the Hawkesbury–Nepean River were studied to identify the effects of two types of riparian vegetation; well‐vegetated banks supporting complex flora dominated by trees and shrubs, and grassed banks, that have been colonised only by grasses after historical deforestation. The fish assemblages showed both spatial and temporal differences and habitats adjacent to grassed banks supported more individuals and more fish species than well‐vegetated banks. Three small species of fish, firetail gudgeon, Hypseleotris galii (Ogilby), flathead gudgeon, Philypnodon grandiceps (Krefft), and empire gudgeon, Hypseleotris compressa (Krefft), occurred in greater abundances adjacent to grassed banks, but freshwater mullet, Myxus petardi (Castelnau), were less abundant near grassed banks than beside well‐vegetated banks. Differences were also shown in the size frequencies of the four larger fish species between riparian vegetation types. The observed differences in the distributions of fish species appeared to be related to the greater abundance aquatic macrophytes near grassed banks, probably an effect of shading of macrophytes near well‐vegetated banks.

Chemical alteration of tephra in the depositional environment: theoretical stability modelling - A. M. Pollard; S. P. E. Blockley; K. R. Ward (Journal of Quaternary Science, 2003)
The study of the chemical stability of vitreous material in aqueous media is well‐established. There has to date been little consideration of the implications of variations in the chemical durability of tephra in Quaternary tephrochronology. Chemical alteration can take the form of cationic leaching from the matrix, or complete destruction of the silica network, either of which could constrain the ability to chemically identify distal tephra. Here we apply established models of vitreous durability to the published chemical analyses of a large number of Icelandic tephras in order to predict their relative durabilities under equivalent conditions. This suggests that some important tephras have relatively poor chemical stability, and that rhyolitic tephras are, in general, more stable than basaltic. We conclude that tephras should be expected to show predictable differential chemical stability in the post‐depositional environment. Copyright © 2003 John Wiley & Sons, Ltd.

Origin of CO 2 -rich fluid inclusions in synorogenic veins from the Eastern Mount Isa Fold Belt, NW Queensland, and their implications for mineralization - G. Xu; P. J. Pollard (Mineralium Deposita, 1999)

Life histories ofPsyllaephagus yaseeni (Hym., Encyrtidae) andTamarixia leucaenae (Hym., Eulophidae), parasitoids of the leucaena psyllidHeteropsylla cubana - N. G. Patil; P. S. Baker; G. V. Pollard (BioControl, 1993)